Elucidating adaptive strategies from leaf anatomy: Do Amazonian savannas present xeromorphic characteristics? - Simioni, Priscila Fernanda; Eisenlohr, Pedro V.; Pessoa, Marcos José Gomes; Silva, Ivone Vieira da (Flora. Morphologie, Geobotanik, Oekophysiologie, 2017)
•Adaptive strategies on Amazonian savannas are investigated.•The hypothesis of fixed characteristics was rejected.•We found a pattern of leaf anatomic structure related to xerophilous habitat.•Plant structure of Amazonian savanna would be shaped by environment determinism. This is among the first studies that associate anatomical characteristics to the environment in the transition region between the two largest phytogeographic domains of South America. We aimed to analyze the leaf anatomy of 22 plant species occurring in the Amazonian savanna in the state of Mato Grosso, Brazil, with the purpose of identifying key characters that show adaptive species strategies in their natural environments. Our hypothesis was that species typical of forest habitats would not present xeromorphic characteristics, while species typical of savanna habitats would present such characteristics. We fixed the samples in FAA50,11FAA 50 (Formaldehyde, Acetic acid and ethyl alcohol). that were stored in alcohol 70%, later they were free-hand cut with a razor blade and stained with astra blue and basic fuchsin. For the analysis of the leaf epidermis, we used the Jeffrey modified method of separation. Characteristics such as thick cuticle, epidermis with thickened wall and straight, presence of silica in the epidermis, tector trichomes, hypostomatic leaves, stomatic crests, dorsiventral mesophyll, presence of collenchyma and vascular bundles were associated with adaptive strategies of the plants to the environment of Amazonian savanna. The anatomic characters presented here are of great importance for the species that live in savanna environments, demonstrating plasticity and contributing to the protection of the leaves to the diverse biotic and abiotic factors to which they are subject, ensuring thus the survival of the species. We demonstrate that plant species structure of Amazonian savanna is most likely shaped by environment determinism, and this fact has implications on how we expect such plants evolve in a climate changing world.